Understanding the Higher Education Experience of Deaf and Hard of Hearing Students: Academic, Social, and Personal Satisfaction - Al-Bakheet, Hibah Nasser A. (Journal of Cultural Analysis and Social Change, 2026)
The experiences of the deaf students and the hearing of higher education and the extent of their satisfaction with this experience provide the opportunity to improve and develop university educational programs and thus increase their chances of enrollment in university education, However, there is limited work in this line of work. This study examines the satisfaction of deaf and hard of hearing students with their educational experiences across academic, social, and personal dimensions in post-secondary education at the University. Using a mixed-methods approach, in the first quantitative phase, the entire study community of (18) students responded to the study questionnaire, whereas the follow up qualitative strand included a purposeful sample of 4 female students, responding to qualitative interviews, to explore their Higher Education experiences. The research tools focused on three key dimensions: academic, social, and personal. Findings revealed a high overall satisfaction level among the participants, with the academic dimension identified as the most satisfying. Students also expressed strong agreement regarding the suitability of the testing environment and the diversity of teaching methods. The limitations of this work and implications for future research and practice are discussed.